"صناديق الإستثمار ودورها في تمويل المؤسسات الصغيرة والمتوسطة - دراسة حالة صناديق الإستثمار في الجزائر " - مسعود, شراحي; محمد الهادي, بوغزالة (unuversity of eloued- جامعة الوادي, 2023)
" إن ""تجربة الجزائر في استخدام صناديق الإستثمار للتمويل محدودة وجد محتشمة""، ونوعا ما خاطئة في القسم الثاني ""لم تأخذ حظها ضمن البرامج والإجراءات التي اتبعتها في مجال تطوير وترقية قطاع المؤسسات الصغيرة والمتوسطة"" بالنسبة لصيغتي رأس المال المخاطر. ولقد أسفرت دراستنا الميدانية على أن المؤسسات الصغيرة والمتوسطة وأصحاب المهن الحرة هم الأكثر طلبا للتمويل عبر صناديق الإستثمار والأكثر استهدافا من قبل المؤسسات الممارسة لها. إن أنشطة التمويل عن طريق صناديق الإستثمار تمارس بشكل مختلف عن مبادئها النظرية التي توافق حاجات المؤسسات الصغيرة والمتوسطة، وهو أحد الأسباب التي تجعل الطلب عليها ضعيفا، بالإضافة إلى غياب الثقافة التشاركية والفكر المغامر لدى المقاولين والمؤسسات الصغيرة والمتوسطة وعدم فهمهم للتقنيات وعدم معرفتهم بالامتيازات المرافقة لها والتحفيزات الحكومية من تسهيلات في الحصول على العقار وضمانات للقروض. ووجدنا أيضا أن صناديق الاستثمار في الجزائر تساهم في تدعيم المؤسسات الصغيرة والمتوسطة، من خلال توفير رؤوس الأموال الكافية في الفترة 2010- 2019 . وتعتمد المؤسسات الصغيرة والمتوسطة في تمويلها على صناديق الإستثمار والوكالات الإستثمارية في الجزائر. وتلعب صناديق الاستثمار دور فعال في تمويل المؤسسات الصغيرة والمتوسطة حيث توجد علاقة تربط صناديق الاستثمار في الجزائر بالمؤسسات الصغيرة والمتوسطة خلال الفترة 2010- 2019 . " " “Algeria’s experience in using investment funds for financing is limited and found to be modest,” and somewhat wrong in the second section, “It did not take advantage of the programs and procedures it followed in the field of developing and promoting the small and medium enterprises sector” with regard to the two forms of risk capital. Our field study revealed that small and medium-sized enterprises and self-employed individuals are the ones who most request financing through investment funds and are the most targeted by the institutions that practice them. Financing activities through investment funds are practiced differently from their theoretical principles that meet the needs of small and medium enterprises, which is one of the reasons why the demand for them is weak, in addition to the absence of a participatory culture and adventurous thinking among contractors and small and medium enterprises, their lack of understanding of the technologies, and their lack of knowledge of the privileges that accompany them and the incentives. The government provides facilities for obtaining real estate and guarantees for loans. We also found that investment funds in Algeria contribute to strengthening small and medium enterprises, by providing sufficient capital in the period 2010-2020. Small and medium enterprises rely on investment funds and investment agencies in Algeria for their financing. Investment funds play an effective role in financing small and medium enterprises, as there is a relationship linking investment funds in Algeria with small and medium enterprises during the period 2010-2020. "
Keywords: صناديق الإستثمار - المؤسسات الصغيرة والمتوسطة - رؤوس الأموال.: investment funds - small and medium enterprises - capital